Social Media Addiction and Mental Health in Adolescents - Rangkuti, Rahmi Putri; Nasution, Indri Kemala; Yurliani, Rahma; Marini, Liza (Universitas Medan Area, 2024)
The article aims to examine the relationship between social media addiction and mental health, especially in adolescents. Social media is one of the platforms widely used by adolescents. Excessive use of social media risks making addiction in its users. Social media addiction is the excessive use of social media that interferes with daily life. Mental health is a state of mental well-being that enables people to cope with the stress in their lives, realize their abilities, learn well and work well, and contribute to their communities. The study used a correlational quantitative method. A total of 333 subjects aged 16-21 years (M = 18.11, SD = 0.88) have participated in the study and filled out the Social Networking Addiction Scale and the Depression Anxiety Stress Scales (DASS) scale which consists of 3 scales namely depression, anxiety and stress. The results of the study using correlation analysis showed a negative relationship between social media addiction and mental health in adolescents (rho=-0.316). Furthermore, social media addiction is positively related to depression, anxiety and stress in adolescents (rho=0.284; 0.297 and 0.318). The research data also showed that 33.04% of the research subjects experienced social media addiction.